2018
DOI: 10.1093/nar/gky875
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule DREEM imaging reveals DNA wrapping around human mitochondrial single-stranded DNA binding protein

Abstract: Improper maintenance of the mitochondrial genome progressively disrupts cellular respiration and causes severe metabolic disorders commonly termed mitochondrial diseases. Mitochondrial single-stranded DNA binding protein (mtSSB) is an essential component of the mtDNA replication machinery. We utilized single-molecule methods to examine the modes by which human mtSSB binds DNA to help define protein interactions at the mtDNA replication fork. Direct visualization of individual mtSSB molecules by atomic force mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 86 publications
(137 reference statements)
2
23
0
Order By: Relevance
“…Previously, we utilized AFM to examine the binding modes of E. coli SSB and human mtSSB to ssDNA. Unlike E. coli SSB, mtSSB does not form nucleoprotein filaments that are a hallmark of cooperative DNA binding but instead binds non-cooperatively to extended ssDNA structures at physiological concentrations of salt (53). The current study utilizes similar solution conditions, and nucleoprotein filaments were not observed in any of our AFM images.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previously, we utilized AFM to examine the binding modes of E. coli SSB and human mtSSB to ssDNA. Unlike E. coli SSB, mtSSB does not form nucleoprotein filaments that are a hallmark of cooperative DNA binding but instead binds non-cooperatively to extended ssDNA structures at physiological concentrations of salt (53). The current study utilizes similar solution conditions, and nucleoprotein filaments were not observed in any of our AFM images.…”
Section: Discussionmentioning
confidence: 76%
“…Analysis of the fractional occupancies (39) of Twinkle along the linear gapped DNA establishes that Twinkle has a high binding specificity (S=KSP/KNSP, ~2.5 x 10 3 ) for the ssDNA gap. In comparison, mtSSB displays a higher binding specificity (S=KSP/KNSP = 1.45 x 10 4 ) determined by the same method (53). Highly specific binding of Twinkle to the ssDNA gap suggested this defined DNA substrate is ideally suited to assess DNA unwinding at the singlemolecule level.…”
Section: Twinkle Binds Ssdna Gaps With High Specificitymentioning
confidence: 94%
See 1 more Smart Citation
“…The precise mode of mtSSB binding is still under investigation. Conflicting reports have provided evidence for both cooperative and non-cooperative binding (Wong TS et al 2009;Miralles Fuste et al 2014;Qian and Johnson 2017;Kaur et al 2018).…”
Section: Mitochondrial Dna Replication Factorsmentioning
confidence: 99%
“…Sequence comparison showed that the major differences between these two proteins are that residues 1–9 and 55–59 of mtSSB are missing in EcoSSB and that EcoSSB contains an additional C-terminal tail missing in mtSSB (11). Apart from these differences, these two SSBs share fast binding (10 9 –10 11 M −1 s −1 ) and slow dissociation (10 −1 –10 −2 s −1 ) kinetics to and from ssDNA (12,13) and bind preformed ssDNA as tetramers in at least two different modes. In each mode, ∼30 (mtSSB 30 ) or ∼60 (mtSSB 60 ) nucleotides are organized per tetramer depending on the salt and protein concentrations (3,12–14).…”
Section: Introductionmentioning
confidence: 99%